PENGARUH TEKNOLOGI INFORMASI DAN KEMAMPUAN KERJA PEGAWAI TERHADAP KUALITAS PELAYANAN MASYARAKAT PADA DINAS KELAUTAN, PERIKANAN, PERTANIAN DAN KEHUTANAN (DKP2K) KOTA BATAM: Program Studi Sistem Informasi, Universitas Putera Batam, Kepulauan Riau. - sasa ani arnomo (Universitas Putera Batam, 2013)
This research discusses about the influence of Information Technology and Civil Servant Work Capability to Quality of Public Services in the Department of Marine, Fisheries, Agriculture and Forestry (DMFAF) Batam City. This study aims to know whether there is and at what impact that Information Technology and Civil Servant Work Capability to Quality of Public Services in the Department of Marine, Fisheries, Agriculture and Forestry (DMFAF) Batam City. The method used in this study is the observation, questionnaires, interviews and a literature review with using data sourced from primary data and secondary data, analysis techniques used in other research is descriptive statistics which includes descriptive data, frequency, histograms and regression analysis, including multiple regression analysis, determination, F test and t test. Based on the results of F test, obtained F calculated is greater than the F table, which means the Information Technology and Civil Servant Work Capability jointly affect the Quality of Public Services, while the t test results, obtained t count bigger than t table on the means of Information Technology partial effect on Quality of society, but t count is less than t table obtained in the Civil Servant Work Capability means that the partial effect of Quality of Public Services.